Construction of ecosystem for electronic component distribution based on platform strategy - Jian SONG (Dianxin kexue)
Inspired by the platformized thinking,it is helpful for domestic electronic component distribution to build an industrial ecosystem by effectively integrating the upstream ICmanufacturer and numerous partner resources tomeet the long tail requirements of the downstream design andmanufacturing companies,which can help the distributors to grow stronger and influential.Starting from the current situation analysis of domestic electronic component distribution industry,the necessity and importance of constructing ecosystem utilizing the platform strategy were explained through the practice of one large electronic component distributor in China.